Maternal complications following open and fetoscopic fetal surgery: A systematic review and meta‐analysis. (27th February 2019) - Sacco, Adalina; Van der Veeken, Lennart; Bagshaw, Emma; Ferguson, Catherine; Van Mieghem, Tim; David, Anna L.; Deprest, Jan
Abstract: Objective: To establish maternal complication rates for fetoscopic or open fetal surgery. Methods: We conducted a systematic literature review for studies of fetoscopic or open fetal surgery performed since 1990, recording maternal complications during fetal surgery, the remainder of pregnancy, delivery, and after the index pregnancy. Results: One hundred sixty‐six studies were included, reporting outcomes for open fetal (n = 1193 patients) and fetoscopic surgery (n = 9403 patients). No maternal deaths were reported. The risk of any maternal complication in the index pregnancy was 20.9% (95%CI, 15.22‐27.13) for open fetal and 6.2% (95%CI, 4.93‐7.49) for fetoscopic surgery. For severe maternal complications (grades III to V Clavien‐Dindo classification of surgical complications), the risk was 4.5% (95% CI 3.24‐5.98) for open fetal and 1.7% (95% CI, 1.19‐2.20) for fetoscopic surgery. In subsequent pregnancies, open fetal surgery increased the risk of preterm birth but not uterine dehiscence or rupture. Nearly one quarter of reviewed studies (n = 175, 23.3%) was excluded for failing to report the presence or absence of maternal complications. Conclusions: Maternal complications occur in 6.2% fetoscopic and 20.9% open fetal surgeries, with serious maternal complications in 1.7% fetoscopic and 4.5% open procedures. Reporting of maternal complications is variable. To properly quantify maternal risks, outcomes should be reported consistently across all fetal surgery studies. Abstract : What's already known about this topic? Fetal surgery, both open and fetoscopic, is now widely performed. Fetoscopy is perceived as safe for the mother, although specific data on maternal complications is lacking. Open fetal surgery is known to cause maternal morbidity, but the exact nature and frequency of complications is not well established across different centres and types of surgery. What does this study add? This study estimates the nature and frequency of maternal complications following fetoscopic and open fetal surgery. For open fetal surgery, the severe complication rate (grades III to V according to the Clavien‐Dindo classification of surgical complications) is approximately 4% and minor complication rate is 16%. For fetoscopic fetal surgery, the severe complication rate is approximately 2% and minor complication rate is 4%.